Can we be Keen Observers - Gupta, V. P. (THE PRIMARY TEACHER, 2006)
Keen and minute observation arouses curiosity, inculcates reasoning and develops a scientific attitude. Keen observation plays a crucial role in learning and in the development of science. Fruits fall from trees naturally but the critical observation of an apple falling from the tree led Newton to discover the important Newton’s Law of Gravitation. Keen observation of things around us and our environment needs concentration and deep and critical thinking. How can we make good observers? How can we motivate students to develop scientific or logical thinking? Let us start this from lower classes, say Class III or IV. National Curriculum Framework 2005. (NCF, 2005) emphasises the importance of learning by listening, observing, interacting, experimenting and analysing, besides reading. Teachers or teacher educators may take up different environmental activities related to the above for development of learning in children. Pimental (1963) quite interestingly introduces his book Chemistry: An Experimental Science with the simple activity of a burning candle.